2020
DOI: 10.1002/agj2.20303
|View full text |Cite
|
Sign up to set email alerts
|

Optimum seeding rate and stand assessment of soft red winter wheat

Abstract: Cultivar selection and seeding rate influence soft red winter wheat (Triticum aestivum L) grain yield. Re-evaluating optimum seeding rate for crops is necessary as modern cultivars may show a greater yield advantage when planted at a higher plant population compared with older cultivars. Furthermore, the relationship between wheat stem population density and yield needs to be understood to help producers make informed estimates of yield potential. The objectives of this research were to determine: (a) the agro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
(49 reference statements)
1
7
1
Order By: Relevance
“…However, H E had an AOSR that was 83% of the Valda yield, suggesting that highly productive hybrids may require a lower seeding rate than inbred cultivars, at least for those included in this trial. Our AOSR results are within the ranges of those for HRSW and winter wheat cultivars of 1.59 to 5.03 and 2.85 to 5.73 and million seeds ha −1 in the northern great plains and Ohio, USA, respectively [25,30]. In Italy, winter wheat hybrids can be planted at 33% of the seeding rate of a conventional cultivar while not losing significant amounts of yield [54].…”
Section: Yieldsupporting
confidence: 74%
See 1 more Smart Citation
“…However, H E had an AOSR that was 83% of the Valda yield, suggesting that highly productive hybrids may require a lower seeding rate than inbred cultivars, at least for those included in this trial. Our AOSR results are within the ranges of those for HRSW and winter wheat cultivars of 1.59 to 5.03 and 2.85 to 5.73 and million seeds ha −1 in the northern great plains and Ohio, USA, respectively [25,30]. In Italy, winter wheat hybrids can be planted at 33% of the seeding rate of a conventional cultivar while not losing significant amounts of yield [54].…”
Section: Yieldsupporting
confidence: 74%
“…The agronomic optimum seeding rate (AOSR) describes the point where the maximum yield is obtained, whereas the economic optimum seeding rate (EOSR) usually includes economic factors associated with the seeding rate and yield to find the point at which the maximum net profit is achieved. When the yield followed a quadratic response to seeding rate, the AOSR was found to be 5.43 million seeds ha −1 and the EOSR to be between 4.24 and 4.83 million seeds ha −1 for winter wheat in Ohio [30]. McKenzie et al [31] reported an EOSR to range from 2.00 to 2.40 million live seeds ha −1 for irrigated soft white spring wheat in southern Alberta, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Wheat N recommendations (in kg N ha –1 ) were calculated by multiplying the yield potential (in kg ha –1 ) by 0.0217 and subtracting 11.2, according to state guidelines (Culman et al., 2020). At WARS, the average yield for winter wheat, according to previously conducted trials, was 5.8 Mg ha −1 (Lindsey et al., 2020), resulting in an N rate of 116 kg N ha −1 for the TM system and 140 kg N ha −1 for the IM treatment. At NWARS, the average yield for winter wheat in previously conducted trials was 5.5 Mg ha −1 (Hankinson et al., 2019), resulting in an N rate of 106 kg N ha −1 for the TM system and 128 kg N ha −1 for the IM system.…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, the recommended seeding rate in Ohio has been 2.96 to 3.95 million seeds ha −1 when planting within 2 wk of the Hessian fly (Mayetiola destructor)-free date . Recently, Lindsey et al (2020) found that modern wheat cultivars responded favorably to increased seeding rates, with the agronomic optimum seeding rate (where grain yield is maximized) being 3.46 to 4.76 million seeds ha −1 with the economic optimum seeding rate (where economic return is maximized) being slightly lower at 2.38 to 3.04 million seeds ha −1 . Likewise, within a no-tillage system in Kansas, an increased seeding rate of 4.0 million seeds ha −1 improved grain yield by approximately 0.4 Mg ha −1 compared with the traditional seeding rate of 2.78 million seeds ha −1 but did not improve economic returns (Jaenisch et al, 2019).…”
mentioning
confidence: 99%
“…Default seeding rates for the wheat MC, wheat (15‐inch row width) with soybean RI, MC soybean, and DC soybean were 1,800,000; 900,000 + 140,000; 140,000, and 200,000 seeds ac −1 , respectively. Seeding rate default values were based on state guidelines (Lindsey et al., 2017a, 2017b) and previously conducted research (Gaspar et al., 2020; Lindsey et al., 2020; Richer & Lindsey, 2016). To convert N fertilizer cost ($ N lb −1 ) to a $ ac −1 basis, N application rate (lb N ac −1 ) was multiplied by the N fertilizer cost.…”
Section: Overview Of the Partial Return Calculatormentioning
confidence: 99%